Ventilator-Associated Pneumonia and PaO2/FIO2 Diagnostic Accuracy: Changing the Paradigm? - Ferrer, M (2019)
BACKGROUND: Ventilator-associated pneumonia (VAP) is associated to longer stay and poor outcomes. Lacking definitive diagnostic criteria, worsening gas exchange assessed by PaO2/FIO2 ≤ 240 in mmHg has been proposed as one of the diagnostic criteria for VAP. We aim to assess the adequacy of PaO2/FIO2 ≤ 240 to diagnose VAP. METHODS: Prospective observational study in 255 consecutive patients with suspected VAP, clustered according to PaO2/FIO2 ≤ 240 vs. > 240 at pneumonia onset. The primary analysis was the association between PaO2/FIO2 ≤ 240 and quantitative microbiologic confirmation of pneumonia, the most reliable diagnostic gold-standard. RESULTS: Mean PaO2/FIO2 at VAP onset was 195 ± 82; 171 (67%) cases had PaO2/FIO2 ≤ 240. Patients with PaO2/FIO2 ≤ 240 had a lower APACHE-II score at ICU admission; however, at pneumonia onset they had higher CPIS, SOFA score, acute respiratory distress syndrome criteria and incidence of shock, and less microbiological confirmation of pneumonia (117, 69% vs. 71, 85%, p = 0.008), compared to patients with PaO2/FIO2 > 240. In multivariate logistic regression, PaO2/FIO2 ≤ 240 was independently associated with less microbiological confirmation (adjusted odds-ratio 0.37, 95% confidence interval 0.15-0.89, p = 0.027). The association between PaO2/FIO2 and microbiological confirmation of VAP was poor, with an area under the ROC curve 0.645. Initial non-response to treatment and length of stay were similar between both groups, while hospital mortality was higher in patients with PaO2/FIO2 ≤ 240. CONCLUSION: Adding PaO2/FIO2 ratio ≤ 240 to the clinical and radiographic criteria does not help in the diagnosis of VAP. PaO2/FIO2 ratio > 240 does not exclude this infection. Using this threshold may underestimate the incidence of VAP.